Trafficking in people in Serbia: Between moral panic and social strategy - Nikolić-Ristanović Vesna Ž. (Temida, 2005)
This paper deals with analysis of different levels of defining understanding, and dealing in general terms with trafficking in people problems in Serbia -from legal regulation and state organs that implement laws in practice, through domestic non-governmental and international organizations, to media images and messages that are sent to the public. The analysis is based on results of up to date research on trafficking in people in Serbia, as well as on author's ongoing monitoring of legal changes and attitudes of media, as well as governmental, non-governmental and international organizations toward this problem.